Platelet-activating factors are associated with cognitive deficits in depressed coronary artery disease patients: a hypothesis-generating study - Mazereeuw, Graham; Herrmann, Nathan; Xu, Hongbin; Figeys, Daniel; Oh, Paul I; AL Bennett, Steffany; Lanctôt, Krista L (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Patients with coronary artery disease (CAD) are at risk of accelerated cognitive decline, particularly those with major depression. Mechanisms for cognitive deficits associated with CAD, and the effects of depression, remain poorly understood. However, CAD is associated with inflammatory processes that have been linked to neurodegeneration, may contribute to cognitive decline, and are elevated in depression. Platelet-activating factors (PAFs) are emerging as key lipid mediators that may be central to those processes and highly relevant to cognitive decline in CAD. Methods This cross-sectional study investigated relationships between various PAFs and cognitive performance in 24 patients with CAD (age, 60.3 ± 9.4; 70.8% male). Analyses were repeated in a subgroup of 15 patients with CAD with major depression (DSM-IV). Cognitive performance was assessed using a standardized battery and summary z scores were calculated based on age, sex, and education norms. Global cognitive performance was the average of domain-specific z scores. Plasma PAF analyses were performed using electrospray ionization mass spectrometry (precursor ion scan). Results A greater abundance of PAF PC(O-18:0/2:0) was associated with poorer global cognitive performance in patients with CAD (r = -0.45, P = 0.03). In the major depressed subgroup, PAF PC(O-18:0/2:0) (r = -0.59, P = 0.02) as well as PC(O-16:0/2:0) (r = -0.52, P = 0.04), and lyso-PAF PC(O-16:0/0:0) (r = -0.53, P = 0.04) were associated with poorer global cognitive performance. A greater abundance of PAF PC(O-19:5/2:0) was associated with better global cognitive performance (r = 0.55, P = 0.03), suggesting a possible compensatory species. Conclusions This study suggests that certain PAFs might be associated with global cognitive performance in patients with CAD, with stronger relationships observed in those with major depression. Confirmation of these preliminary findings is warranted.